The Molar Extraction Debate: Adhuc sub iudice lis est (Sciendo, 1994)
Recent reports of conflict between dentists and orthodontists over the extraction of second molar teeth prior to orthodontic treatment raise a number of questions; one of which is: not whether or not to extract, hut which teeth to extract.